2020
DOI: 10.2147/ijwh.s228738
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effects of Labor Epidural Analgesia on Short Term Neonatal Morbidity</p>

Abstract: Background: Epidural Analgesia (EA) is the most effective and most commonly used method for pain relief during labor. Some researchers have observed an association between EA and increased neonatal morbidity. But this observation was not consistent in many other studies. Objectives: The primary objective of the study was to examine whether exposure to epidural analgesia increased the risk of NICU admission. The secondary objectives included the risks of clinical chorioamnionitis, instrumental delivery, neonata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 75 publications
(115 reference statements)
2
16
0
Order By: Relevance
“…Based on the results of our own research, it was found that the age of women who used epidural anesthesia is significantly lower than those who did not. In a study conducted in Qatar (Asia) by Salameh K. et al [19], the same conclusions were found, however, their result was not statistically significant. In contrast, Antonakou A. et al [20] noted that English women with epidural anesthesia were significantly older.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Based on the results of our own research, it was found that the age of women who used epidural anesthesia is significantly lower than those who did not. In a study conducted in Qatar (Asia) by Salameh K. et al [19], the same conclusions were found, however, their result was not statistically significant. In contrast, Antonakou A. et al [20] noted that English women with epidural anesthesia were significantly older.…”
Section: Discussionmentioning
confidence: 56%
“…Salameh K. et al [19] noted that the gestational age in the group of women who used epidural anesthesia is significantly higher compared to women who were not anaesthetized. Our study also confirmed this result as statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…The confounding factor in this study may be related to the difference in the percentage of epidural analgesia (EA) between groups. Some literature data indicate that EA correlates with increases neonatal care unit admission of newborns (OR 1.89, 95% CI 1.45 to 2.46), respiratory distress (OR 1.49, 95% CI 1.07 to 2.07) and need for oxygen in first day of life (OR 1.44, 95% CI 1.01 to 2.07) [ 21 ]. However, literature data do not indicate an increased risk of acidosis in children born during deliveries with EA [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epidural anesthesia during delivery is the most common and widely accepted method of pain relief during labor [ 1 3 ]. Although the proportion of pregnant women requesting pain control with anesthesia varies internationally between 20%-70% [ 2 , 3 ], the proportion in Japan continues to be relatively low.…”
Section: Introductionmentioning
confidence: 99%